Estimating Specular Roughness and Anisotropy from Second Order Spherical Gradient Illumination - Ghosh, Abhijeet; Chen, Tongbo; Peers, Pieter; Wilson, Cyrus A.; Debevec, Paul (Computer graphics forum, 2009)
This paper presents a novel method for estimating specular roughness and tangent vectors, per surface point, from polarized second order spherical gradient illumination patterns. We demonstrate that for isotropic BRDFs, only three second order spherical gradients are sufficient to robustly estimate spatially varying specular roughness. For anisotropic BRDFs, an additional two measurements yield specular roughness and tangent vectors per surface point. We verify our approach with different illumination configurations which project both discrete and continuous fields of gradient illumination. Our technique provides a direct estimate of the per‐pixel specular roughness and thus does not require off‐line numerical optimization that is typical for the measure‐and‐fit approach to classical BRDF modeling.